2010
DOI: 10.1074/jbc.m109.086553
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of the Ca2+-activated K+ Channel, KCa2.3, Is Dependent upon RME-1, Rab35/EPI64C, and an N-terminal Domain

Abstract: Regulation of the number ofFurthermore, the effect of EPI64C was dependent upon its GTPase-activating proteins activity. Co-immunoprecipitation studies confirmed an association between KCa2.3 and both Rab35 and RME-1. In contrast to KCa2.3, KCa3.1 was rapidly endocytosed and degraded in an RME-1 and Rab35-independent manner. A series of N-terminal deletions identified a 12-amino acid region, Gly 206 -Pro 217 , as being required for the rapid recycling of KCa2.3. Deletion of Gly 206 -Pro 217 had no effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(137 citation statements)
references
References 46 publications
10
123
1
Order By: Relevance
“…7,8 Recent studies demonstrate that various K + channel proteins undergo endocytosis and degradation, that is, the ATP-sensitive K + channel, 9 or K Ca 3.1. 10,11 However, K + channel degradation has been reported in HEK cells in which K + channels are not endogenously expressed but exogenously expressed by transfection; future studies are required to confirm these results on endogenously expressed K + channels in native cells. Our previous study showed that excessive Gb3 impairs the endothelial expression and activity of K Ca 3.1, and that Gb3-induced K Ca 3.1 downregulation is at least in part caused by a defect in the synthesis of this channel protein.…”
Section: See Accompanying Editorial On Pagementioning
confidence: 88%
See 1 more Smart Citation
“…7,8 Recent studies demonstrate that various K + channel proteins undergo endocytosis and degradation, that is, the ATP-sensitive K + channel, 9 or K Ca 3.1. 10,11 However, K + channel degradation has been reported in HEK cells in which K + channels are not endogenously expressed but exogenously expressed by transfection; future studies are required to confirm these results on endogenously expressed K + channels in native cells. Our previous study showed that excessive Gb3 impairs the endothelial expression and activity of K Ca 3.1, and that Gb3-induced K Ca 3.1 downregulation is at least in part caused by a defect in the synthesis of this channel protein.…”
Section: See Accompanying Editorial On Pagementioning
confidence: 88%
“…K Ca 3.1 degradation has been reported in cells in which K Ca 3.1 was not endogenously expressed but exogenously expressed by transfection. The exogenously expressed K Ca 3.1 proteins were rapidly endocytosed from the plasma membrane to endosomes 10 and degraded in lysosomes. 11 However, the regulation of the internalization and degradation/recycling of the endogenous K Ca 3.1 in native cells has not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the N termini of K Ca 2.3 and K Ca 3.1 play an important role in shuttling them to the proteasome for degradation with a different mechanism (54,55). Gao et al (54) have clarified that S3/S4 domains are essential for the degradation of K Ca 3.1 proteins.…”
Section: N Terminus Of K Ca Critical For Channel Trafficking To Plasmmentioning
confidence: 99%
“…Once activated by its specific GEFs, the connecdenn/DENND1 family of proteins (Allaire et al, 2010;Marat and McPherson, 2010), Rab35 drives the recycling of a wide variety of cargo including MHC class I (Allaire et al, 2010) and MHC class II (Walseng et al, 2008), T-cell receptor (Patino-Lopez et al, 2008), the calcium activated potassium channel KCa 2+ 2.3 (Gao et al, 2010), exosomes ) and synaptic vesicles (Uytterhoeven et al, 2011). Rab35 also functions during cell division to recycle lipid and protein components necessary for furrow ingression (Kouranti et al, 2006;Dambournet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%